Dynamic model development : methods, theory, and applications : proceedings from a Workshop on the Life of a Process Model–from Conception to Action, October 25-26, 2000, Imperial College, London, UK /: methods, theory, and applications : proceedings from a Workshop on the Life of a Process Model–from Conception to Action, October 25-26, 2000, Imperial College, London, UK. (2003) - Unknown
No abstract available